INNOVATIVE APPROACHES TO THE DEVELOPMENT OF MARKETING IN THE UNIVERSITY ECOSYSTEM IN THE CONTEXT OF MODERN CHALLENGES - Фастовець, Наталія В.; Ганущак-Єфіменко, Людмила М.; Кахраманоглу, Алі; Бал Інджебаджак, Бельгін; Яман, Сулейман (Journal of Strategic Economic Research, 2025)
The article explores the concept of university ecosystem marketing development in the context of modern global challenges, including globalization, digitalization, post-pandemic adaptation, and political and economic instability. The main problems affecting the competitiveness and sustainability of universities are identified, among which the outflow of intellectual potential, inequality in access to digital resources, and limited funding are particularly highlighted. The experience of leading world universities is analyzed, in particular the practices of the Massachusetts Institute of Technology and Stanford University, which are actively implementing digital platforms, micro-qualifications, innovative pedagogical approaches, and partnerships with business to ensure the quality of education and its global attractiveness. The article analyzes the role of digital tools in shaping the competitiveness of universities, in particular through the implementation of online platforms that ensure the accessibility of educational programs to a wide audience, reduce the digital divide, and stimulate international cooperation in the university ecosystem. Examples of successful partnerships between universities and businesses that promote investment attraction, development of innovative entrepreneurship and creation of innovative university infrastructure are considered. Strategies are proposed that promote equal access to education for socially vulnerable groups, a strategy for developing the marketing of the university ecosystem, which is formed on the basis of a digital educational environment, the development of adaptive educational programs, active partnership with business and the implementation of marketing campaigns aimed at popularizing the existing university innovation potential, are substantiated. As a result, it is noted that the implementation of these approaches will contribute to the transformation of universities into innovation centers capable of integrating into the global educational space, accumulating intellectual potential and contributing to the innovative sustainable development of society.